Cockle shell as a cheap and renewable catalyst for the production of biodiesel / Zainal Kifli Abdul Razak, Syamsyir Akmal Senawi and Kurniadi Muhtar - Abdul Razak, Zainal Kifli; Senawi, Syamsyir Akmal; Muhtar, Kurniadi (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
The global energy crisis has inspired scientists to search for alternative fuels to replace the current fossil fuels. One of the solutions is to produce biodiesel which is a potential energy source to replace the petroleum-based diesel. Biodiesels are produced from biological sources and are thus renewable. In chemical terms biodiesels are fatty acid methyl esters (FAME) or fatty acid ethyl esters (FAEE). They are produced by a reaction called transesterification. Transesterification is a reaction where a plant-based or animal-based oil/fat reacts with methanol or ethanol to produce FAME or FAEE. This reaction needs a catalyst, otherwise it proceeds very slowly. At present various chemical such as hydrochloric acid, sodium hydroxide or potassium hydroxide are used as the catalyst. In this invention cockleshells are used to produce the catalyst for the production of biodiesel from rubber seed oil. Cockleshell is a cheap and renewable material and is available in abundance since cockle is a common food in Malaysia. In this project the cockle shell was converted to calcium oxide by heating it in a furnace at 700 oC for 2 hours. Calcium oxide acts as the catalyst for the transesterification of rubber seed oil to produce biodiesel. The reaction is carried out by adding calcium oxide to a mixture of rubber seed oil and methanol. After heated and stirred for 2 hours the reaction produces biodiesel in the form of FAME.